Correlation between productive components and grain yield of soybean cultivars sown in the northwest region of Rio Grande do Sul - Paraginski, João Antônio; Poll Moraes, Mariana; Rodrigues de Souza, Rafael; de Carvalho Mello, Anderson; Toebe, Marcos (Revista Ceres, 2024)
Considering the expressive number of commercial soybean cultivars available for cultivation in Brazil and the constant search for improvements in the production system, the objective was to evaluate the productive components and grain yield and to estimate the correlation between them in soybean cultivars sown in the northwest region of Rio Grande do Sul, during the 2019/20 harvest. Sixteen commercial soybean cultivars were sown under their respective plant density recommendations, in a randomized block design with three replications. At the end of the cultivation cycle, the following variables were evaluated: plant height; height of insertion of the first pod; number of nodes; number of pods with one, two, three and four grains; pods per plant; grains per plant; weight of thousand grains, and; grain yield. The cultivars BMX ZEUS IPRO, NS 5445 IPRO and NS 5700 IPRO presented the highest grain yields, mainly due to the high relationship between the number of pods and grains per plant and the weight of a thousand grains. The indirect selection of more productive genotypes can be carried out through the variables weight of thousand grains, number of pods, grains and nodes per plant, given the significant positive correlation between them.